Pendampingan Dosen IPB Mengabdi Menuju Wisata Pertanian Kota, Kota Bogor - Adi Supriyatno; Aji Hermawan; Sugeng Heri Suseno (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
This activity conduct to help the preparation of people included in Posdaya group to build the urban agricultural tourism, and also exploring the natural potentials that can be utilized by the community. Hopefully those aims could grow the economic sectors of Bogor City. The method used within this activity are Active Participation, Accompaniment and Training Forms, targeted the people included in Posdaya group. The result of this activity is to make sure that people who are included in Posdaya group have been established and ready in technically or either non-technically to make any changes or movements towards the urban agricultural tourism of Bogor City. Beautiful natural resources is a potential that can be used by the community to attract tourists to visit the location so they could grow the economic sector in the community.